Evaluation of regional transformation parameters between the SAD69 and SIRGAS2000 systems - Oliveira, José Venâncio Marra (2020)
The objective of this paper, in the first instance, concerned about to analyze the differences found in the coordinate transformation parameters between the SAD69 and SIRGAS2000 systems of all RBMC stations spread throughout Brazil and the proposal to adopt regional transformation parameters that may be compatible with the reference point. Requested to IBGE the reports of all the geodetic stations of the RBMC of the year 2014 and it was considered only the active stations throughout the Brazilian territory. To realize the comparison between the SAD69 and SIRGAS2000 systems, the geodetic coordinate’s transformations were performed for cartesian coordinates of each station of the RBMC, of its respective system, and were organized by region. The results showed that the application of the transformation technique of reference systems is satisfactory, but showed that centimeters differences between the transformation parameters (translation) and that the regional parameter averages were close to the values adopted for the country.